Recent Advances in Laboratory Diagnosis of Syphilis - Zarakolu, Pınar (Mikrobiyoloji bülteni, 2023)
Syphilis is a sexually transmitted disease caused by Treponema pallidum subsp. pallidum. This historical disease has diverse clinical manifestations making laboratory testing crucial for optimal patient management. Direct detection of T.pallidum by dark-field microscopy is possible when lesions are present. Culture of the bacteria is complex and not performed routinely. There is no well-validated commercially available polymerase chain reaction (PCR) test. Serological tests are currently the most common diagnostic methods adapted in clinical laboratories. They provide a presumptive diagnosis and used for screening, diagnosis, and follow-up of the treatment. They are divided into two groups, named as nontreponemal and treponemal tests and performed by the application of the traditional algorithm, the reverse sequence algorithm or European Centre for Disease Prevention and Control (ECDC) algorithm. The traditional algorithm starts with a nontreponemal test and a reactive result is confirmed with a treponemal test. In the reverse sequence algorithm, a treponemal test is used for screening and a reactive result is confirmed by a quantitative nontreponemal test. When the nontreponemal test is negative, a second different treponemal test preferably T.pallidum particle agglutination test (TPPA) is used. The ECDC algorithm recommends screening by a treponemal test such as T.pallidum enzym immunoassay (TP-EIA), T.pallidum chemiluminescence immunoassay (CIA) and if reactive, a reflex confirmatory treponemal test is performed. The treponemal tests become reactive a few weeks after infection and remain reactive even after successful treatment. The nontreponemal tests are used to assess disease activity and response to therapy. Serological tests have many limitations such as false-positivity, falsenegativity in various stages of the disease and also challenging difficulties when evaluating response to therapy. In recent years, rapid syphilis tests which are mostly treponemal-specific tests have been developed for high-prevalence populations in resource limited settings. There has been requirement for the utility of standart PCR and IgM testing in the diagnosis of congenital syphilis and neurosyphilis cases. In this review article, it was aimed to present the diagnostic tests, the algorithms, the correct indications for testing and interpretation of the test results to the likely corresponding clinical stage of the disease with in the perspective of recent advances.